Wychowanie w świetle filozofii Fryderyka Nietzschego - Janas , Adam (Studia Edukacyjne, 2022)
If education were an epistemologically open conceptual construct, then in places going beyond its conceptualism it would point beyond itself to the ineffable, and therefore over-conceptual. Thinking about education through its mediation in the light, power and essence of what appears to be, seems to be an opportunity to participate in different orders of existence. As a consequence, the concept of education, if it points beyond itself, reveals a horizontally dispersed and vertically united, diverse space of a possibly eternal universe. The view of this space, as originally over- and pre-conceptual, eludes all systemic thought yet stemming from it, because it always reveals itself as an over-completeness of what is conceptually conceived. Education therefore appears as ennobling and life-giving participation in various orders of existence. The aim of this article will be to develop the above vision of education in the light of Friedrich Nietzsche’s philosophy, however, supplementing this research with Plato’s philosophy when Nietzsche’s deliberations prove to be insufficient.